2019
DOI: 10.1029/2019jb017835
|View full text |Cite
|
Sign up to set email alerts
|

Deep Crustal Faults, Shear Zones, and Magmatism in the Eastern Cordillera of Colombia: Growth of a Plateau From Teleseismic Receiver Function and Geochemical Mio‐Pliocene Volcanism Constraints

Abstract: The Eastern Cordillera of Colombia, in the northern Andes, is an example of an orogen in which Mesozoic basins were compressed during the Cenozoic, forming a ~2,500‐m‐high plateau in its northern portion. Significant shortening and crustal thickening have contributed to the construction of the present topography and elevation. In this contribution, we combine the use of teleseismic receiver functions, Hf isotopes, whole‐rock geochemistry, and U‐Pb dating to help elucidate the main mechanisms that played a role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 72 publications
(138 reference statements)
3
12
0
Order By: Relevance
“…Such a feature is only observed in this part of the EC. These LVL might correspond to partial melts accumulating either along mid-crustal detachment faults, or in magma chambers under the Paipa-Iza volcanic complex, as has been suggested in previous studies (e.g., Bernet et al, 2016;Monsalve et al, 2019;Poveda et al, 2018). The presence of magma at crustal depths is consistent with the slow S-wave velocities (Poveda et al, 2018), high Vp/Vs ratios (Poveda et al, 2015), and high Lg attenuation (Ojeda & Ottemoller, 2002) found for this area.…”
Section: Eastern Cordillerasupporting
confidence: 87%
“…Such a feature is only observed in this part of the EC. These LVL might correspond to partial melts accumulating either along mid-crustal detachment faults, or in magma chambers under the Paipa-Iza volcanic complex, as has been suggested in previous studies (e.g., Bernet et al, 2016;Monsalve et al, 2019;Poveda et al, 2018). The presence of magma at crustal depths is consistent with the slow S-wave velocities (Poveda et al, 2018), high Vp/Vs ratios (Poveda et al, 2015), and high Lg attenuation (Ojeda & Ottemoller, 2002) found for this area.…”
Section: Eastern Cordillerasupporting
confidence: 87%
“…Successful detections of present-day mantle plumes using P-wave and/or S-wave velocity anomalies include the work of, for example, Montelli et al (2004) and Civiero et al (2019). These results suggest that the currently active plumes are characterized by negative velocity anomalies, associated with the presence of high-temperature material.…”
mentioning
confidence: 86%
“…The northern margin of the South American plate is an active zone with two flat-slab subductions that interact at depth: the Nazca (Coiba microplate) plate from the west and the Caribbean plate from the north (some recent references include Bernal-Olaya et al, 2015;Chiarabba et al, 2015;Monsalve et al, 2019;Porritt et al, 2014;Siravo et al, 2019;Syracuse et al, 2016;Vargas and Mann, 2013;Wagner et al, 2017;Yarce et al, 2014). This complex interaction defines a poorly understood tectonic setting.…”
Section: Nazca and Caribbean Subductionsmentioning
confidence: 99%
“…The northern margin of the South American plate is an active zone with two flat-slab subductions which interact at depth: the Nazca (Coiba microplate) plate from the west and the Caribbean plate from the north (some recent references include: Bernal-Olaya et al, 2015;Chiarabba et al, 2015;Monsalve et al, 2019;Porritt et al, 2014;Siravo et al, 2019;Syracuse et al, 2016;Vargas and Mann, 2013;Wagner et al, 2017;Yarce et al, 2014). This complex interaction defines a poorly understood tectonic setting.…”
Section: Nazca and Caribbean Subductionsmentioning
confidence: 99%